A comparative study of two open-source state-of-the-art geometric VOF methods. (15th January 2023) - Esteban, Adolfo; López, Joaquín; Gómez, Pablo; Zanzi, Claudio; Roenby, Johan; Hernández, Julio
Abstract: We present a systematic study of geometric volume of fluid (VOF) methods provided in the gVOF and TwoPhaseFlow packages, which include algorithms that are among the most accurate proposed in recent years. In addition to contributing to their further validation, the main purpose is to evaluate, in terms of accuracy and efficiency, the relative advantages of the advection and reconstruction algorithms used in the two packages (mainly, FMFPA-CLCIR and isoAdvector-plicRDF, respectively), and to investigate the suitability of combining them. Since TwoPhaseFlow is available in OpenFOAM, gVOF was also coupled with this open source CFD toolbox to maintain the same conditions in common solvers when obtaining and comparing their results, including discretization schemes, tolerances and meshes. For the same reason, identical computational resources were also maintained. The use of a common software and hardware framework that guarantees strictly the same simulation conditions overcomes many of the limitations and uncertainties of comparisons made in previous studies. Several reconstruction and advection tests are presented, showing the differences between the algorithms in terms of accuracy, as measured by several error norms, and in terms of efficiency, as measured by CPU times consumed. Simulations of the rise of a bubble and the impact of a drop on a pool were also performed, in which the VOF methods were coupled to the same solver of the Navier–Stokes equations, and the results obtained with the two combinations of algorithms FMFPA-CLCIR and isoAdvector-plicRDF are compared with each other and, in the case of the second test, with our own experimental results. The relative advantages and limitations of the analyzed algorithms are discussed, and it is suggested that a combination of isoAdvector for advection and CLCIR for reconstruction can provide a good compromise between accuracy and efficiency. Highlights: Efficiency and accuracy of advanced geometric volume of fluid methods are assessed. Rigorous comparison ensured by keeping same common solvers and simulation settings. Errors and CPU times compared in several advection and reconstruction tests. Methods performance when coupled to a Navier–Stokes solver evaluated experimentally. A combination of methods proposed to provide a good accuracy/efficiency compromise.